Cohort study examining social determinants of health and their association with mortality among hospitalised adults in New York and California - Andrew Wang; Abel N Kho; Dustin French; Bernard Black (BMJ Public Health)
Background Adults in the US face significant disparities in health as a result of the social determinants of health (SDOH). While the link between SDOH and mortality is well-established, their impact on outcomes after hospitalisation is less understood.Methods Among adults aged 18–84 years hospitalised in New York (NY) during the period of 2000–2009 and in California (CA) from during the period of 2000–2006, we examined the association between 1-year post-hospitalisation mortality and a community-level SDOH combined index (comprising six component domains) using Kaplan-Meier survival analysis and multivariable Cox proportional-hazard models to estimate the mortality HR (adjusted HR (aHR)) adjusted for age, gender, race, ethnicity and Charlson Comorbidity Index. We also studied subcohorts in NY and CA grouped by hospitalisation conditions (subgroups with chronic or acute disease).Results In NY, the overall 1-year mortality rate was 8.9% (9.7% for chronic diseases and 13.2% for acute diseases). In CA, the overall 1-year mortality rate was 8.3% (12.6% for chronic diseases and 15.8% for acute diseases). In both states, the 1-year risk of death was significantly lower for those in the best (Q4) SDOH (combined index) compared with the worst (Q1 is the reference category). In NY, the aHR was 0.964 (p<0.001 and 95% CI 0.950 to 0.978), while in CA, the aHR: 0.83 (p<0.001 and 95% CI 0.825 to 0.842). Similar patterns were observed for the disease cohorts in both states. The Economic and Education domains of SDOH showed stronger and more consistent associations with mortality risk compared with the domains of Neighbourhood, Food Access, Community and Social Context, and Healthcare.Conclusions This study demonstrates a significant association between worse SDOH and higher post-hospitalisation mortality. The findings emphasise the importance of community-level SDOH in patient care planning and discharge strategies to reduce health disparities.